Physlet physics : - Christian, Wolfgang (Prentice Hall, 2004)
For courses in Introductory Physics. This book and CD package furnishes students with a host of interactive, computer-based exercises and study resources that span the entire introductory physics curriculum. Using a practical yet engaging structure, Physlet(R) Physics presents a wide spectrum of "media-focused" critical thinking and problem-solving exercises, and provides students with an interactive visual representation of the physical phenomena they see in introductory physics textbooks.